EFEKTIVITAS PROGRAM PENDIDIKAN AUTISMA LONDON SCHOOL BEYOND ACADEMY (LSBA) DALAM MEMPERSIAPKAN INDIVIDU AUTISMA SIAP KERJA - Erni Adi Astuti; Hotner Tampubolon; Nurul Hidayah (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2021)
This research are conducted to explore the curriculum planning, to expose the implementation of the curriculum in LSBA that is effective for individuals with autism, to determine the process of monitoring teaching and learning activities and to determine the process of evaluating the results of teaching and learning activities at LSBA. The research method used is descriptive with a qualitative approach, which is describing the data obtained from the field and explaining in words. This study aims to find what the most effective program for individuals with autism who graduated from high school. In addition, this study explores more deeply the implementation of the curriculum and the learning techniques applied in the London School Beyond Academy (LSBA). This research found that the effectiveness of curriculum planning, the effectiveness of curriculum implementation carried out properly during teaching and learning activities in class, the effectiveness of monitoring teaching and learning activities carried out is in accordance with the program planning but the additional term of study is needed and the effectiveness of the evaluation of teaching and learning activities has been carried out well in LSBA for individuals with autism. The conducted reearch also found that the program implemented at LSBA is effective for individuals with autism who are ready to work with the skills they have after studying in LSBA. The more effective the educational program, the more it will support individuals with autism ready to work according to their respective abilities. Keywords: education program effectiveness, planning, implementation, monitoring, evaluation, individuals with autism